Telemedicine use among neurologists before and during COVID-19 pandemic - Aquino, Emanuelle Roberta da Silva; Domingues, Renan Barros; Mantese, Carlos Eduardo; Fantini, Francisca Goreth Malheiro Moraes; Nitrini, Ricardo; Prado, Gilmar Fernandes do (Arquivos de Neuro-Psiquiatria, 2021)
Background: After the public health emergency due to COVID-19 was declared in Brazil, the federal government temporarily regulated and authorized the use of telemedicine services for patient consultation, monitoring, and diagnosis. For more than a decade, neurologists have recognized the benefits of telemedicine in the acute management of stroke patients. However, as the use of telemedicine was restricted until the COVID-19 pandemic, the view of Brazilian neurologists about telemedicine is unknown. Methods: All neurologists registered at the Brazilian Academy of Neurology were invited by e-mail to participate in a survey about personal perceptions on telemedicine use. Results: One hundred sixty-two neurologists from all regions of Brazil answered the online questionnaire. The survey showed that 18.5% of participants worked with telemedicine before the pandemic, while 63.6% reported working with telemedicine during the pandemic. The main telemedicine modalities used during the pandemic were teleorientation and teleconsultation. Discussion: According to our data, the COVID-19 pandemic deeply influenced the behavior of Brazilian neurologists, who developed a more favorable view about telemedicine and actively searched for information about telemedicine. As there is a need for more training in this area in Brazil, universities and medical societies must strive to improve telemedicine education. Expanding the use of high-quality teleneurology can contribute to a better care for patients with neurological diseases in Brazil.
Keywords: Telemedicine; Neurology; COVID-19; Teleneurology; Remote consultation